Paul, the Praetorium and the Saints from Caesar's Household: Philippians Revisited in Light of Migration Theory. (June 2021) - Omerzu, Heike
This article premises that Paul wrote the letter to the Philippians while he was detained in Ephesus, not Rome as has been the traditional view, and that the πραιτώριον mentioned in Phil. 1.13 is a topographical reference – that is, a reference to a Roman administrative building, not the Imperial Guard in Rome. This πραιτώριον is likely also the place where Paul met the members of 'Caesar's household' mentioned in Phil. 4.22. Engaging with Michael Flexsenhar III's recent study Christians in Caesar's Household (2019a), I explore the social profile of this group of imperial slaves as well as Paul's place as a social actor in the Eastern Mediterranean in light of recent trends in Migration Studies. Both Paul himself and also the members of the familia Caesaris to whom he refers embody typical features of migration such as interconnectedness, multiple belongings and super-diversity; these are shown to be important prerequisites for Paul's conception of early Christian identity formation.